2018
DOI: 10.1159/000486626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Moisturizer Application in Different Ethnic Skin Types: Noninvasive Assessment with Optical Coherence Tomography and Reflectance Confocal Microscopy

Abstract: Background/Aims: Ethnic skin types are known to differ in their morphological and physiological features. Thus, treatment responses may vary among different races. We aimed to assess skin morphology of different ethnicities and to compare the effect of short-term moisturizer application using optical coherence tomography (OCT) and reflectance confocal microscopy (RCM). Methods: Thirty healthy female subjects of European, Asian and Black ethnicity at 30–45 years of age were included in the study. OCT and RCM im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
2
10
1
Order By: Relevance
“…Concerning skin morphology and blood vessels analysis, we reported an increase in BF at a depth of 0.3 mm between timelines T1 and T2 in the treated arm, probably due to mechanical stimulation causing vasodilatation. Accordingly, we saw a significant decrease in the skin roughness parameters (Ra and Rz) between baseline and T1 only in the moisturized arm, indicating a smoothening of the skin surface, in line with our previous study 33 . We found no statistically significant changes in the AC; in particular, we could not observe the expected decrease of AC observed in other studies after treatment with glycerol, probably because our measurements were not taken immediately after moisturizing 39 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning skin morphology and blood vessels analysis, we reported an increase in BF at a depth of 0.3 mm between timelines T1 and T2 in the treated arm, probably due to mechanical stimulation causing vasodilatation. Accordingly, we saw a significant decrease in the skin roughness parameters (Ra and Rz) between baseline and T1 only in the moisturized arm, indicating a smoothening of the skin surface, in line with our previous study 33 . We found no statistically significant changes in the AC; in particular, we could not observe the expected decrease of AC observed in other studies after treatment with glycerol, probably because our measurements were not taken immediately after moisturizing 39 …”
Section: Discussionsupporting
confidence: 90%
“…Reflectance confocal microscopy (RCM) provides high‐resolution horizontal imaging of epidermis and papillary dermis enabling assessment of cellular details. In our previous study assessing the same moisturizing lotion in different ethnic skin types, we observed a reduced width of skin folds following 2 weeks application of the same moisturizing lotion on the treated arms as compared to the control arms using RCM 33 . On the other hand, Manfredini et al.…”
Section: Discussionmentioning
confidence: 73%
“…The epidermis of intensely pigmented samples is low dyskeratotic and vacuolated compared to samples of the epidermis of more minor pigmented. Although there is no discernible skin thickness difference between white and black skin, black skin possesses more corneocytes in the stratum corneum than white skin, implying a more dense and compacted layer [75, 76]. Black skin has a higher mean electrical resistance than white skin, which is most likely due to this compaction [77].…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in skin hydration are common among patients with diabetes [34]. Less hydration has been associated with thinner skin and measurements of skin, derma, and fat can be affected by different hydration statuses [35]. We did not evaluate skin hydration in this study; however, it could modify the results.…”
Section: Discussionmentioning
confidence: 99%